STATE SUPPORT FOR ENTREPRENEURSHIP DEVELOPMENT IN ITALY - Sypko, Vladyslav (Social Economics, 2022)
Abstract. Entrepreneurship is a very important part of economic development, which is why the level of its efficiency reflects the development of the country as a whole. State support of enterprises of various sizes allows to advance the level of the economy a few steps forward and thus strengthen the economic stability of the country. The article describes the state of Italy’s economic development since the 1950s and the methods by which the state supported and developed entrepreneurship and eventually became one of the world’s most developed leaders. The results of the study showed that after the Second World War, Italy suffered greatly and, in order to boost the economy, used the strategy of developing state-owned enterprises with further liberalization. Since the 2000s, Italy has intensified its policy of non-interference, the main idea of ​​which is the self-balance of the economy as a whole, by introducing relevant legislation. Despite significant progress, problems have arisen in some areas, in particular with small and medium-sized farms, which are very important in the economy. Research has shown that there is almost no state support in this area and it is very difficult for farmers to start their own business. In addition, the situation is similar with young start-ups, their main problem being the lack of funding, which Italy has now partially solved by implementing a microfinance system. I found that the share of small and medium enterprises in Italy is the largest, and they have a strong impact on economic performance, so their support from the state is necessary for their full functioning and maximum efficiency. Also in the article, I assessed the effects of COVID-19 and found that the pandemic hit the economy hard, reducing GDP by 9.5%. Such a sharp decline is also due to the cost of supporting businesses and the public during coronavirus infection. In addition, I described the methods by which the country spreads the interest of ordinary people in business. I also gave examples of Italy’s participation in projects aimed at developing and supporting entrepreneurship and creating certain grants that should help student entrepreneurs who do not have enough investment to start their own business.